DESIGN AND FABRICATION OF ELECTRIC BIKE WITH SLIDING FRAME - Sumbodo, Wirawan; Wahyudi; Setiadi, Rizki; Kriswanto; Budiman, Febrian Arif (Journal of Applied Engineering Science, 2021)
Transportation is important for humans. Generally, the means of transportation use machines that can pollute the environment. The use of fuel oil which is used as a driving force for vehicles can be the main cause of the release of various pollutants. Emissions generated by internal combustion engines can cause many losses. Losses due to emissions include losses on health, the environment, and economic impacts. Besides, the amount of fuel oil resources is decreasing every year. For that to anticipate this need development electric bike. The campus environment, especially that of the more established universities, has entered the public consciousness as being a haven for electric bike use. The main advantages of electric bikes are economical and environmentally friendly. The objectives of this study were (1) to design an electric bike, (2) to analyze the strength of the sliding frame of an electric bike, (3) to test the distance traveled by an electric bike. The research method used research and development. The results of the research are (1) an electric bike design with a sliding frame has been created, (2) the results of the frame analysis using iron material, the von mises stress 49.98 MPa, a maximum displacement of 0.125 mm, and a safety factor is 3. (3) Based on the test track, an electric bike using a sliding frame can travel a distance of 75 km with a maximum speed of 25 km/hour.